Changing systems for saving lives : result area 1 : understanding the health situation - Philippines. Department of Health Davao Region (Manila : DOH, KOICA, USAID, WHO, 2018)
Contents: Developing the program monitoring frameworks and the regional health dashboards -- Assessing the functionality of inter-local health zones -- Facility readiness and service
Keywords: Maternal Health; Infant Health